Malting Performance of Landrace Barley and Wheat Grown in Nigeria Using Long and Short Steeping Regimes. (3rd April 2023) - Agu, R. C.; Amadi, O. C.; Nwagu, T. N.; Moneke, A. N.; Okolo, B. N.
Abstract: A longer steeping regime is advocated when malting elite barleys. A shorter steeping regime used in this study produced good hot water extract (HWE), fermentability, fermentable extract (FE), free amino nitrogen (FAN), peptide nitrogen (PN), and predicted spirit yield (PSY) from malted and mashed barley and wheat. High germination energy (GE)–germination test and good germination performance during the malting process resulted in the production of good quality malt. A high nitrogen content (less starch), lower screening of grains >2.5 mm (thin grains) of barley and wheat, and especially, the high husk (14.8%) of the barley further confirmed that mashing thin grains can cause lower PSY from the malted barley or wheat. The steeping regime influenced glucose to maltose ratios, resulting in higher glucose to maltose ratios. The glucose to maltose ratio is important for effective yeast fermentation. Complimentary results from FAN and PN supported yeast fermentation. Malted barley gave higher PSY results at both steeping regimes. Malted Nigerian-grown wheat gave higher PSY results than imported wheat, when short or longer steeping was used in malt production. This could be linked to differences in the starch structures in the wheat samples studied. The shorter steeping produced good quality malt. This could save costs in terms of energy use, water use, and carbon dioxide release from respiring embryos during steeping and germination. For optimum advantage of the shorter stepping regime to be achieved, good quality grain must be selected to reap the full benefit in using a shorter steeping regime to produce good malt.